A case report of COVID-19 with multiple comorbidities with a positive outcome in early days of COVID-19 outbreak in Bangladesh (BIRDEM Medical Journal, 2020)
We present a case of 68-year-old man with diabetes, heart failure, status post-coronary artery bypass grafs, cardiac resynchronization therapy defibrillator in situ, altered liver function, with corona virus disease 2019. He presented with cough and high grade fever with occasional dyspnea. He was treated at home with favipiravir, methyl prednisolone, enoxaparin and antibiotics and home oxygen therapy. He re-tested positive on 14th and 21st day and later on 31st day he was found RT-PCR negative for SARS-CoV-2. Patient came for a follow-up after 3 months in healthy state with normal D-dimer and other inflammatory markers.Birdem Med J 2020; 10, COVID Supplement: 131-134